Pertussis – Morbidity, Immunization Tactics and Diagnostic Methods in Various European Countries - E. V. Bakhmutskaya; A. Ya. Mindlina; A. V. Stepenko (Эпидемиология и вакцинопрофилактика, 2018)
The paper reviews the incidence of pertussis, immunization tactics and diagnostic methods in 8 countries in the European Regionin 2001–2016. The surveyed countries were selected based on the  incidence of whooping cough: high, relatively high, medium and low. The results obtained showed that the reduction in the incidence of  whooping cough is typical for those European countries where the  immunization against pertussis regimen includes additional  revaccinations of preschool and pregnant women, as well as when coverage of the primary vaccination series exceeds 95%. With the growth of inapparent and not typical forms of the course of whooping  cough, the use of only the bacteriological method of diagnosis does not show the true morbidity.